Study on forming tool module with variable stiffness blank-holder for applications in high strength steel and laser welding parts - Faria, C. (2019)
This study presents experimental and numerical results of a development prototype tool that includes blank-holder plates of variable stiffness. The application is analyzed for high-strength steel parts and tailor welded blanks manufactured from dissimilar steel grades using laser welding. A numerical model was constructed within the Ansys software platform incorporating appropriate material constitutive models parameters for high-strength Dual-Phase steels. The obtained results show a positive control of springback geometries. Experimental tests were performed on the relevant geometries. The presented numerical and experimental results constitute a validation of a variable-stiffness blank-holder approach for this particular case study.